1986
DOI: 10.7601/mez.37.59
|View full text |Cite
|
Sign up to set email alerts
|

Studies on filariasis VII : Histological observation on the encapsulated Brugia malayi larvae in the abdominal haemocoel of the mosquitoes, Armigeres subalbatus

Abstract: The JapanSociety

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Three‐day‐old adult female Armigeres subalbatus were used because Kobayashi et al . (1986) demonstrated that nearly 95% of Dirofilaria immitis microfilariae (mf) inoculated into this mosquito species are melanized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three‐day‐old adult female Armigeres subalbatus were used because Kobayashi et al . (1986) demonstrated that nearly 95% of Dirofilaria immitis microfilariae (mf) inoculated into this mosquito species are melanized.…”
Section: Methodsmentioning
confidence: 99%
“…Mosquitoes Three-day-old adult female Armigeres subalbatus were used because Kobayashi et al (1986) demonstrated that nearly 95% of Dirofilaria immitis microfilariae (mf) inoculated into this mosquito species are melanized. Furthermore, Christensen et al (1986) demonstrated that parasite melanization by mosquitoes is related to age, and younger mosquitoes have a better parasite melanization ability.…”
Section: Methodsmentioning
confidence: 99%
“…Armigeres subalbatus were obtained from the Center of Disease Control, Taipei, Taiwan, and have been kept in the insectary there since 1992. Microfilariae were obtained from dogs experimentally infected with Dirofilaria immitis, isolated from the blood by membrane filtration, and intrathoracically inoculated as previously described (Kobayashi et al, 1986;Liu et al, 1997).…”
Section: Mosquitoes and Filarial Wormsmentioning
confidence: 99%
“…subalbatus rapidly induces a melanization defense response and destroys naturally invading Brugia malayi microfilariae, but is permissive to the complete development of the closely related parasite, Brugia pahangi (Kobayashi et al, 1986;Beerntsen et al, 1989;Zhao et al, 1995). This mosquito species also kills, by melanotic encapsulation, 95% of Dirofilaria immitis microfilariae by melanotic encapsulation within 2 days following intrathoracic inoculation (Christensen et al, 1984).…”
Section: Introductionmentioning
confidence: 96%